Boganmeldelser - Ingrid Sahlin; Peter Lindström; Henrik Stevnsborg; Anita Rönneling; Hreinn S. Hákonarson; Leif Petter Olaussen; Janne Flyghed; Jens Frederik Skovsgard Kragholm; Peter Garde; Paul Larsson (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews